Multiple brillouin stokes generation with bismuth-based erbium-doped fiber - Shahi, Sharifeh; Harun, Sulaiman Wadi; Dimyati, Kaharudin; Tamjis, Mohamad Rom; Ahmad, Harith (John Wiley & Sons, 2010)
A multiple Brillouin Stokes generation is demonstrated at extended L-band region using the bismuth-based erbium-doped fiber (Bi-EDF) in the linear cavity. A 2.15-m long Bi-EDF is used to provide both nonlinear and linear gains to generate a stimulated Brillouin scattering (SBS) and to amplify the generated SBS, respectively. The Brillouin erbium fiber laser operates at 1615 nm region with more than 40 Stokes and anti-Stokes lines, and the line spacing is measured to be similar to 0.09 nm. Based on the four-wave mixing signals spacing, the dispersion coefficient of the Bi-EDF is estimated to be,similar to 95 ps/nm/km. (C) 2010 Wiley Periodicals, Inc. Microwave Opt Technol Lett 52: 1416-1418, 2010; Published online in Wiley InterScience (www.interscience.wiley.com). DOI 10.1002/mop.25207